Crime Prevention in the Classroom: Gendered Impacts on Offending - O, SooHyun (Crime & delinquency, 2024)
This study examines school-based crime prevention tactics using a place management framework in conjunction with deterrence and labeling theoretical perspectives. We examine the effects of four different aspects of place management on student offending and explore whether and how the effects are distinctive for female versus male students. We analyze survey data from students and principals across three waves of the Rural Substance abuse and Violence Project using multilevel-binomial models. Findings reveal that several aspects of place management interacted with gender, thus differentially impacting male versus female offending. Overall, this study extends past work in providing evidence of the gendered impact of some crime prevention practices?conditional effects that are consistent with insights from both deterrence and labeling theoretical perspectives.